Rock music culture, aesthetics, and sociology - Wicke, Peter (Cambridge University Press, 1990)
Rock music - powerful, sensual, loud and full of energy. It has changed the face of modern music. But what is its fascination for, and its significance in contemporary society and what cultural values does it reflect? Peter Wicke addresses these issues in a stimulating and penetrating study of rock music tracing the genesis and influence of this diverse strand of popular music. Beginning with the advent of rock 'n' roll, Wicke chronicles the development through Elvis Presley and the Beatles to the current music industry, its performers, and the impact of the music video. The book will appeal to readers with an interest in music history, popular culture, and media studies
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Gesellschaft; Musik; Rock music / History and criticism; Music / Philosophy and aesthetics; Music / Social aspects; Popular culture